2018
DOI: 10.1016/j.taap.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic and glucocorticoid receptor antagonists reduce ozone-induced lung injury and inflammation

Abstract: Recent studies showed that the circulating stress hormones, epinephrine and corticosterone/cortisol, are involved in mediating ozone-induced pulmonary effects through the activation of the sympathetic-adrenal-medullary (SAM) and hypothalamus-pituitary-adrenal (HPA) axes. Hence, we examined the role of adrenergic and glucocorticoid receptor inhibition in ozone-induced pulmonary injury and inflammation. Male 12-week old Wistar-Kyoto rats were pretreated daily for 7days with propranolol (PROP; a non-selective β a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 72 publications
(90 reference statements)
4
44
0
Order By: Relevance
“…Effects of ozone inhalation are not limited to the respiratory system. Our results support the previous observation that ozone exposure reduces circulating WBC, especially lymphocytes, while increasing circulating epinephrine and corticosterone in rats (Henriquez et al, 2018;Miller et al, 2016b). Since CLENþDEX also produces a substantial reduction in circulating lymphocytes (likely due to the immunosuppressive dose of DEX) while increasing BALF neutrophils, it is likely that these effects of ozone are modulated by stress hormones in a dynamic and cellspecific manner (Dhabhar et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Effects of ozone inhalation are not limited to the respiratory system. Our results support the previous observation that ozone exposure reduces circulating WBC, especially lymphocytes, while increasing circulating epinephrine and corticosterone in rats (Henriquez et al, 2018;Miller et al, 2016b). Since CLENþDEX also produces a substantial reduction in circulating lymphocytes (likely due to the immunosuppressive dose of DEX) while increasing BALF neutrophils, it is likely that these effects of ozone are modulated by stress hormones in a dynamic and cellspecific manner (Dhabhar et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…As we have noted in previous publications (Henriquez et al, 2018), ozone exposure was also associated with BALF NAG activity (a marker of macrophage activation) increases in vehicletreated SH rats at D þ 2. AD diminished this ozone effect at D þ 2 ( Figure 5F).…”
Section: Circulating Stress Hormones Are Changed After Ozone Exposuresupporting
confidence: 80%
See 1 more Smart Citation
“…1C, D), confirming a role for the HPA axis in mediating and modifying local and systemic effects of ozone exposure [54]. More recently, evidence of adrenal stress hormone involvement was further substantiated in a study that showed that administration of adrenergic and glucocorticoid receptor antagonists prior to and concurrent with exposure modified the pulmonary response to ozone [55]. The relevance of these observations to humans was confirmed in a panel study that showed that controlled exposure to 0.2 ppm ozone increased plasma stress hormone levels [56].…”
Section: The Hpa Axis: Air Pollutants As Stressorsmentioning
confidence: 82%
“…These molecules mediate platelet, neutrophil, and mononuclear infiltration into the lungs (Berman & Muller, 1950;Grommes et al, 2012;Schenkel, Chew, Chlipala, Harbord, & Muller, 2006). Animal models have also helped characterize potential mechanisms of pulmonary (Dowell, Lohrbauer, Hurst, & Lee, 1970;Michaudel, Fauconnier, Jule, & Ryffel, 2018) Bhattacharya & Westphalen, 2016) as well as multiple organ injury (Bouthillier et al, 1998;Erickson et al, 2017;Henriquez et al, 2018;Kasahara et al, 2014;Thomson, Pilon, Guenette, Williams, & Holloway, 2018) resulting from O 3 exposure. These studies show that a 3-6 hr exposure to 0.8 or 2 ppm O 3 induces recruitment and accumulation of lung monocytes and neutrophils at 24 hr (Francis et al, 2017;Tighe et al, 1950).…”
mentioning
confidence: 99%